2020
DOI: 10.1007/s00442-020-04721-w
|View full text |Cite
|
Sign up to set email alerts
|

Trophic position, elemental ratios and nitrogen transfer in a planktonic host–parasite–consumer food chain including a fungal parasite

Abstract: Parasitism is arguably the most commonly occurring consumer strategy. However, only a few food web studies assess how well stable isotopes reflect the trophic position of parasitic consumers and results are variable. Even fewer studies have measured the nutrient transfer by parasitic consumers, hindering an assessment of their role in nutrient transfer through food webs. Here we used a food chain consisting of a diatom as host, a chytrid as its parasitic consumer and a rotifer as the predatory consumer of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 64 publications
4
21
0
Order By: Relevance
“…The viral shunt has been estimated to liberate 2 to 10% of photosynthetic C to the DOC pool during viral-induced cell lysis ( 81 ), thereby stimulating C transfer from phytoplankton to free-living bacteria ( 82 ) and thus microbe-mediated remineralization ( 83 , 84 ). As opposed to the viral shunt, we suggest that parasitic chytrids shunt photosynthetic C to the particulate organic C pool since we demonstrated that C is most efficiently transferred to attached sporangia, and the therein developed zoospores, which, as shown previously, are grazed by micro- and mesozooplankton ( 23 27 ). Moreover, chytrid infections accelerated diatom decay, stimulating bacterial colonization (by potentially opportunistic bacteria that thrive on decaying organic particles).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The viral shunt has been estimated to liberate 2 to 10% of photosynthetic C to the DOC pool during viral-induced cell lysis ( 81 ), thereby stimulating C transfer from phytoplankton to free-living bacteria ( 82 ) and thus microbe-mediated remineralization ( 83 , 84 ). As opposed to the viral shunt, we suggest that parasitic chytrids shunt photosynthetic C to the particulate organic C pool since we demonstrated that C is most efficiently transferred to attached sporangia, and the therein developed zoospores, which, as shown previously, are grazed by micro- and mesozooplankton ( 23 27 ). Moreover, chytrid infections accelerated diatom decay, stimulating bacterial colonization (by potentially opportunistic bacteria that thrive on decaying organic particles).…”
Section: Discussionsupporting
confidence: 72%
“…A recent concept, called mycoloop, describes parasitic chytrids as an integral part of aquatic food webs ( 22 ). Energy and organic matter are thereby transferred from large, often inedible phytoplankton to chytrid zoospores, which are consumed by zooplankton ( 23 27 ). Hence, parasitic chytrids establish a novel trophic link between phytoplankton and zooplankton.…”
mentioning
confidence: 99%
“…CC-BY 4.0 International license available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is made consequences for carbon and nutrient cycling as mediated by the fungal shunt 33,34 . The possibility of fungal parasitism on algae in epilithic biofilms further underlines the role of photoautotrophs as the foundation of a complex food web in GFSs as a typically energy-limited ecosystem.…”
Section: Metagenomics Unveils the Complexity Of Epilithic Biofilmsmentioning
confidence: 99%
“…Furthermore, our results hint at the existence of a more cryptic interaction in epilithic biofilms between parasitic fungi Chytridiomycetes and algae (i.e., Ochrophyta). Fungal parasitism on pelagic algae has been recently reported to be more important than expected, even with consequences for carbon and nutrient cycling as mediated by the fungal shunt 33,34 . The possibility of fungal parasitism on algae in epilithic biofilms further underlines the role of photoautotrophs as the foundation of a complex food web in GFSs as a typically energy-limited ecosystem.…”
Section: Metagenomics Unveils the Complexity Of Epilithic Biofilmsmentioning
confidence: 99%
“…Parasitism is a widespread lifestyle, with ~40% of all organisms having at least one parasitic life-stage. Accounting for parasitic relationships, ~75% of food web interactions involve a parasite (Dobson et al 2008) causing increases in linkage density (Lafferty et al 2008;Sánchez Barranco et al 2020), food chain length (Amundsen et al 2009), and connectance (Dunne et al 2013). Contributions of parasite biomass to an ecosystem can be substantial and even exceed that of top predators (Kuris et al 2008;Preston et al 2013).…”
Section: Introductionmentioning
confidence: 99%